2012
DOI: 10.4103/0019-5413.93684
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis of the elbow: A clinicoradiological analysis

Abstract: Background:The incidence of Tuberculosis (TB) of elbow is 2-5% of all skeletal locations. Most reports of TB elbow have focused attention on the diagnosis. The management options and classification has been missing. We present a retrospective clinicoradiological analysis of 38 cases (40 elbows) of TB of elbow joint.Materials and Methods:The patients presented with pain, swelling and loss of motion. Two cases had bilateral involvement. The average delay between onset of symptoms and presentation was 8 months. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…In the study by Vohra et al [15], all patients had pain and restricted motion (n= 10), and 7 patients had swelling. Similar results were reported by Dhillon et al [14]. In the present study, pain was the most common presentation (100%) followed by restricted motion (93%) and local swelling (71.5%).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the study by Vohra et al [15], all patients had pain and restricted motion (n= 10), and 7 patients had swelling. Similar results were reported by Dhillon et al [14]. In the present study, pain was the most common presentation (100%) followed by restricted motion (93%) and local swelling (71.5%).…”
Section: Discussionsupporting
confidence: 92%
“…In other studies, enlarged lymph nodes were reported in one third to all the patients [16,17]. In the study by Dhillon et al [14], the supratrochlear (n=4) and axillary (n=3) lymph nodes were reported. Vohra et al [15] reported supratrochlear and/or axillary lymph nodes involvement in 4 cases.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations